2019
DOI: 10.2169/internalmedicine.2177-18
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary Nocardiosis Caused by <i>Nocardia exalbida</i> in a Patient with Lung Cancer and Radiation Pneumonitis: A Case Report and Literature Review

Abstract: We report a case of Nocardia exalbida ( N. exalbida )-induced pneumonia in a 70-year old Japanese man with lung cancer and radiation pneumonitis. He initially received doripenem (1.5 g/day) for pneumonia treatment, and N. exalbida was identified by a clone library analysis of bronchoalveolar lavage fluid obtained from the pneumonia lesion. The doripenem dosage was therefore increased to 3.0 g/day with adjunctive trim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…Only 3 out of 7 patients had fever, so fever is not always present in nocardiosis patients. Multisite abscesses includes subcutaneous, pulmonary and cerebral abscesses [ 42 , 43 ], which are commonly misdiagnosed as pneumonia or tuberculosis or even as lung cancer or metastatic tumors. Considering that direct extrinsic contact and inhalation are the main routes of Nocardia infection, subcutaneous and lung tissues are the most frequently affected sites of nocardiosis [ 44 , 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…Only 3 out of 7 patients had fever, so fever is not always present in nocardiosis patients. Multisite abscesses includes subcutaneous, pulmonary and cerebral abscesses [ 42 , 43 ], which are commonly misdiagnosed as pneumonia or tuberculosis or even as lung cancer or metastatic tumors. Considering that direct extrinsic contact and inhalation are the main routes of Nocardia infection, subcutaneous and lung tissues are the most frequently affected sites of nocardiosis [ 44 , 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…A search tool algorithm for basic local comparisons was used to perform a homology search (15). This is generally considered the gold standard for bacterial identification (16,17). However, rRNA gene sequencing fails to discriminate between some species of Nocardia, likely because DNA-DNA hybridization studies have shown there is high sequence similarity between Nocardia species (18).…”
Section: Discussionmentioning
confidence: 99%
“…N. exalbida infection might be associated with a good response to treatment [ 16 ]. In one case that had pneumonia with N. exalbida with HIV the patient was treated with TMP/SMX six tablet (approximately 12 mg per kg of body weight) for the TMP component) monotherapy for 12 month and cure [ 14 ].…”
Section: Discussionmentioning
confidence: 99%